2004
DOI: 10.1161/01.str.0000126039.91400.cb
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of the Human Cerebral Microcirculation During Aneurysm Surgery Reveals Increased Arteriolar Contractility

Abstract: Background and Purpose-The effects of aneurysmal subarachnoid hemorrhage on morphology and function of the cerebral microcirculation are poorly defined, partly due to the lack of suitable techniques to visualize the microvessels in vivo. We used orthogonal polarization spectral (OPS) imaging on the brain cortex during aneurysm surgery to directly observe the small cortical blood vessels and quantify their responses to hypocapnia. Methods-In 16 patients undergoing aneurysm surgery, the diameter changes of small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 22 publications
5
69
1
2
Order By: Relevance
“…Taken together, the current study shows that in-vivo subarachnoid/pial arterioles show the same pearl string-like constrictions that have been previously observed in humans (Uhl et al, 2003;Pennings et al, 2004), that these constrictions are frequent (70% of all arterioles) and severe enough ( > 30%) to cause ischemia, and that arteriolar constrictions seem to trigger the formation of microthrombosis and microvascular stasis, thereby further aggravating tissue perfusion. Although the detailed molecular mechanisms underlying this phenomenon still need to be investigated, the current results suggest that long-lasting hemodynamic alterations at the microcirculatory level may be an important mechanism for the development of early post hemorrhagic ischemia, which is of utmost im portance for the prognosis of patients experiencing SAH.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Taken together, the current study shows that in-vivo subarachnoid/pial arterioles show the same pearl string-like constrictions that have been previously observed in humans (Uhl et al, 2003;Pennings et al, 2004), that these constrictions are frequent (70% of all arterioles) and severe enough ( > 30%) to cause ischemia, and that arteriolar constrictions seem to trigger the formation of microthrombosis and microvascular stasis, thereby further aggravating tissue perfusion. Although the detailed molecular mechanisms underlying this phenomenon still need to be investigated, the current results suggest that long-lasting hemodynamic alterations at the microcirculatory level may be an important mechanism for the development of early post hemorrhagic ischemia, which is of utmost im portance for the prognosis of patients experiencing SAH.…”
Section: Discussionsupporting
confidence: 85%
“…This means that the cerebral microcirculation can be visualized without any previous mechanical alterations to the cerebral vasculature and under conditions of physiological cerebrospinal fluid flow. This procedure may explain why this is the first experimental study to observe the pearl string-like pattern of arteriolar constrictions so far only observed in humans (Uhl et al, 2003;Pennings et al, 2004).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…OPS has recently been introduced in the clinical setting to image distinctive microvascular and hematological pathologies associated with different disease states, including (cardio)vascular diseases, cancer, and sepsis [2][3][4]. The imaging technique allows the observation of vascular structures and endovascular constituents (red blood cells and leukocytes) at high contrast [5], and facilitates quantitative measurements of physiological parameters (red blood cell velocity, vasomotion) as well as pathophysiological conditions (ischemia/reperfusion, hemorrhage, tumor angiogenesis) without requiring contrast enhancers or fluorescent dyes [3,[6][7][8][9][10]. In OPS imaging, vascularized tissue is illuminated with linearly polarized light, while the remitted light is imaged through an analyzer (second polarizer) oriented orthogonally to the polarizer.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, microvascular spasms could be noticed during the surgery while vasospasm was not yet detected by usual techniques. Another study (40) showed increased contractile responses of the cerebral arterioles in the presence of subarachnoid blood (and induced by hypocapnia), suggesting increased microvascular tonus.…”
Section: Head Trauma and Subarachnoid Hemorrhagementioning
confidence: 96%